Progressive multifocal leukoencephalopathy: analysis of lesion development with diffusion-weighted MRI. - Mader, I; Herrlinger, U; Klose, U; Schmidt, F; Küker, W (2003)
Progressive multifocal leukoencephalopathy (PML), caused by replication of JC virus in oligodendrocytes of immunocompromised patients, is diagnosed by polymerase chain reaction-based demonstration of JC virus DNA. We investigated whether MRI might be used to assess disease activity. Diffusion-weighted imaging (DWI) was obtained in two patients with PML, in whom it was the only MRI sequence on which we could identify areas of progressive disease. The extent of abnormal diffusion appeared to correlate with the speed of clinical progression. DWI would thus seem to be of value in patients with PML.